Examining ecotourism intention: The role of tourists' traits and environmental concerns - Rafiq, Farrukh; Adil, Mohd; Wu, Jei-Zheng (Frontiers in Psychology, 2022)
This study examines the role of two personality traits (extraversion and neuroticism) in motivating consumers to adopt ecotourism. We also determine environmental concern’s role in assessing personality traits and ecotourism intention. In addition, the role of environmental knowledge in moderating the paths leading to ecotourism intentions was also tested. This study collected primary data using the M-Turk platform. According to the results, extroverts are more likely to express ecotourism intentions than neurotic tourists. Results highlight that neurotic tourists intend to visit ecotourism sites after introducing environmental concerns. Further, environmental knowledge bridges the concern-behavior gap in the ecotourism domain. The results indicate that environmental knowledge and concern play a significant role in determining individuals’ environmental behavior and help in converting tourists’ neurotic orientation into pro-environmental behavior.